Computational fluid dynamics applied to competitive swimming: The role of finger position - Marinho, D. A.; Barbosa, T. M.; Kjendlie, P. L.; Reis, V. M.; Vilas-Boas, J. P.; Machado, L.; Rouboa, A. I.; Silva, A. J. (Biomechanics and Medicine in Swimming XI - Abstracts, 2010)
INTRODUCTION: The best fingers relative position during the underwater path of the stroke cycle in swimming seems to be a unclear issue. Even in elite level swimmers, different relative positions of thumb and finger spreading can be observed. The aim of the current abstract was to present the hydrodynamic characteristics of a true model of a swimmer's hand with different fingers' positions using computational CFD. METHODS: Scans of the right hand of a male elite swimmer were obtained using a computer tomography scanner. The hand was scanned with fully abducted (68o), partially abducted (30o) and adducted thumb positions (Marinho et al., 2009). Furthermore, scans were made with fingers closed together, fingers with little distance spread (0.32 cm) and fingers with large distance spread (0.64 cm) (Marinho et al., 2010). Steady-state CFD analyses were performed using the FluentR code. The measured forces on the hand models were decomposed into drag and lift coefficients (CD and CL). Attack angles of hand models of 0o, 45o and 90o, with a sweep back angle of 0o were used. RESULTS: The position with the thumb adducted presented slightly higher CD values compared with thumb abducted positions (0o, CD=0.25; 45o, CD=0.61; 90o, CD=1.09). The position with the thumb fully abducted presented higher CL values at attack angles of 0o (CL=0.24 vs. CL=0.21, partially abducted; CL=0.18, abducted) and 45o (CL=0.65 vs. CL=0.62, partially abducted; CL=0.60, adducted). The model with little distance between fingers (0o, CD=0.24; 45o, CD=0.68; 90o, CD=1.13); presented igher CD values than the models with fingers closed (0o, CD=0.25; 45o, CD=0.61; 90o, CD=1.09) and fingers with large distance spread (0o, CD=0.26; 45o, CD=0.57; 90o, CD=0.93). The values for the lift coefficient presented little differences between the three models, for a given attack angle (0o, CL.0.20; 45o, CL.0.60; 90o, CL.0.20). DISCUSSION: For hand positions in which the lift force can play an important role (e.g. insweep phases), the abduction of the thumb may be better, whereas at higher angles of attack, in which the drag force is dominant, the adduction of the thumb may be preferable. Moreover, these thumb positions should be associated to fingers slightly spread, allowing the hand to create more propulsive force during swimming.